Vascular Anomalies of the Head and Neck: Diagnosis, Imaging, and Treatment - Beydoun, Tammam; Aria, David; Curran, John; Towbin, Richard (Journal of Pediatric Neuroradiology, 2016)
Vascular anomalies are congenital errors in vascular developments frequently involving the head and neck. Imaging often plays a pivotal role in the diagnosis requiring familiarity by the interpreting radiologist in order to best guide management. Multidisciplinary teams are essential in managing this group of pathologies. In a community setting, the radiologist may be the first encounter wherein the patient has the best chance of being appropriately referred to the dedicated team of specialists. Divided into malformations and tumors, we review their presentation with imaging correlation, natural history, and discussion of current treatment strategies focusing on the more common subcategories. Taking into consideration the physical and psychosocial effects of these diseases, swift diagnosis and appropriate treatment significantly improves quality of care and prognosis.
Keywords: vascular malformation; hemangioma; arteriovenous malformation; lymphatic malformation